Melissopalynological analysis of forest honey from north Malaysia - Izzah Nasuha Rosdi; Kirthiga Selvaraju; Paritala Vikram; Kumara Thevan Krishnan; Mohammed Arifullah (Universiti Malaysia Kelantan, 2016)
Honey is a natural product widely used by humans due to its sweet taste and health benefits produced by bees from nectar and honey dew of various plants. To establish and increase the production of honey one must know the plants that take part in the production of honey. In this study pollen analysis of forest honey samples from northern part of Malaysia was carried out to determine the botanical sources playing role in the production of honey in that region. The pollen samples were acetolyzed and identified microscopically. Out of the three samples studied Baling sample was unifloral having Mimosa scabrella as predominant pollen while Jeli and Gerik samples are multifloral containing Tipo myrcia and Elais guineensis as major secondary pollen. Fabaceae family represented four pollen types and accounted 80% of pollen in Baling sample and 34 % in Gerik sample while completely absent in Jeli sample. These results showed the dominance of plants from Fabaceae family in honey production. All the samples analysed have Albizia falcataria, Eupatorium sp., Sparganium typha, Tilia sp. and Tipo myrcia in common indicating that these plants are present in all the three places and these results also can be used as a tool in geographical identification of North Malaysian honey from others.